Field-Dependent Stiffness of a Soft Structure Fabricated from Magnetic-Responsive Materials: Magnetorheological Elastomer and Fluid - Song, Byung-Keun (Materials (Basel), 2020)
A very flexible structure with a tunable stiffness controlled by an external magnetic stimulus is presented. The proposed structure is fabricated using two magnetic-responsive materials, namely a magnetorheological elastomer (MRE) as a skin layer and a magnetorheological fluid (MRF) as a core to fill the void channels of the skin layer. After briefly describing the field-dependent material characteristics of the MRE and MRF, the fabrication procedures of the structure are provided in detail. The MRE skin layer is produced using a precise mold with rectangular void channels to hold the MRF. Two samples are produced, namely with and without MRF, to evaluate the stiffness change attributed to the MRF. A magnetic field is generated using two permanent magnets attached to a specialized jig in a universal tensile machine. The force-displacement relationship of the two samples are measured as a function of magnetic flux density. Stiffness change is analyzed at two different regions, namely a small and large deformation region. The sample with MRF exhibits much higher stiffness increases in the small deformation region than the sample without MRF. Furthermore, the stiffness of the sample with MRF also increases in the large deformation region, while the stiffness of the sample without MRF remains constant. The inherent and advantageous characteristics of the proposed structure are demonstrated through two conceptual applications, namely a haptic rollable keyboard and a smart braille watch.